HEALTH INSURANCE MEMBERSHIP IN INDONESIAN LAND TRANSFERS: A REVIEW OF LEGAL AND POLICY IMPLICATIONS - Sunarno, Sunarno; Rahmania, Mar'atush Shalehah (Universitas Syiah Kuala, 2025)
The enactment of Presidential Instruction Number 1 of 2022, on Optimizing the Implementation of the National Health Insurance Program, introduces a requirement for proof of National Health Insurance (BPJS Kesehatan) participation from all citizens during land rights transfers. This study examines the legal implications of this instruction, focusing on its validity, relevance, and social impact on public access to land rights. Employing a doctrinal approach, the research involved legal document reviews, policy analysis, and interviews with relevant stakeholders. The findings indicate that mandating BPJS membership as a condition for land transfer registration is legally invalid, irrelevant, and conflicts with Indonesias constitutional hierarchy. This inconsistency leads to legal uncertainty and undermines the principle of orderly regulation, creating overlapping regulations, unclear authority between the National Land Agency (BPN) and BPJS Kesehatan, and potential institutional conflicts. It increases administrative burdens that could restrict citizens access to legitimate land rights. Overall, the study argues that this instruction risks undermining legal hierarchy and good governance principles, which could adversely affect public access to land and hinder effective policymaking. It highlights the importance of understanding Indonesias legislative hierarchy to prevent policies from disrupting existing legal structures. To mitigate these issues, it is recommended that the government revise Presidential Instruction Number 1 of 2022, ensuring alignment with legislative hierarchy, and foster dialogue and collaboration among relevant institutions for the development of comprehensive, non-conflicting policies.